The Berenstain Bears safe and sound! - Berenstain, Jan, 1923-2012.; Berenstain, Mike, 1951- (New York : HarperFestival, 2009)
Brother and Sister Bear are happy to ride their skateboards at the skate park, but when it closes Brother and Sister are embarrassed to wear their helmets among the skaters at the other park.
"Ages 3-7"--Cover p. [4].
2.9
K-3
K-3
Keywords: Berenstain Bears (Fictitious characters) -- Juvenile fiction; Skateboarding -- Juvenile fiction; Safety education -- Juvenile fiction; Embarrassment -- Juvenile fiction; Berenstain Bears (Fictitious characters) -- Fiction; Skateboarding -- Fiction; Safety -- Fiction; Embarrassment -- Fiction; Berenstain Bears (Fictional characters) -- Fiction; Skateboarding -- Fiction; Safety education -- Fiction; Self-consciousness -- Fiction